Characterization of Biocomposites from Polylactic Acid and Cellulose of Oil Palm Empty Fruit Bunch - Tika Paramitha; Johnner P Sitompul (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Biocomposites are polymers reinforced with natural fibers, such as cellulose. This research aims to synthesize cellulose from Oil Palm Empty Fruit Bunch (OPEFB) and biocomposites from PLA and cellulose. In this study, cellulose was obtained through alkalization, hydrolysis, and bleaching of OPEFB. Biocomposites production was carried out by mixing PLA and cellulose using the extrusion method. In the extrusion method, PLA and cellulose of OPEFB were mixed using an extruder above the melting point of PLA of 170°C. The output product of an extruder was then pressed using a compression moulding machine to form biocomposites. The tensile strength of biocomposites had a smaller value than pure PLA, whereas the modulus young of biocomposites with 5% by weight of cellulose had a higher value than pure PLA. The decrease in the mechanical properties of biocomposites was caused by poor adhesion between PLA and cellulose. The water absorption of biocomposites was greater than pure PLA, which was influenced by cellulose's characteristics as hydrophilic and PLA is hydrophobic. Also, the higher water absorption in biocomposites accelerated the weight loss of biodegradability.